Air pollution in Astana: analysis of recent trends and air quality monitoring system. (2018) - Kerimray, Aiymgul; Bakdolotov, Aidyn; Sarbassov, Yerbol; Inglezakis, Vasileios; Poulopoulos, Stavros
Abstract: Astana is the capital and the fastest growing city in Kazakhstan, with more than two-fold population growth in the last 15 years. This increase in population is inevitably connected to rapidly growing energy consumption and increased numbers of transport vehicles, which in turn have an impact on the air quality of the city; the air pollution levels of Astana seem to reach a critical condition. However, there is a lack of studies reviewing the air quality in Astana. In the present work, it is shown that pollutant levels of PM10, NO2, SO2, and Total Suspended Particles are highly elevated in Astana, and exceed both the annual limit values set by WHO and EU, and standards adopted in Kazakhstan